Philosophy of Development
VIII, 296 p.
Keywords: Philosophy of development is a fascinating area of research at the intersection of philosophy, psychology, and education. This book is unique in that it combines a broad sketch of contemporary developmental theory with detailed discussions of its central issues, in order to construct a general framework for understanding and analyzing theories of individual and collective development in various domains ranging from cognitive and moral development to developments in art. Special attention is also given to the rich relations between conceptual development and education.